Lack of Male-Female Differences in Disposition and Esterase Hydrolysis of Ramipril to Ramiprilat in Healthy Volunteers after a Single Oral Dose - Tom B. Vree; Erik Dammers; Ivan Ulc; Stefan Horkovics-Kovats; Miroslav Ryska; IJsbrand Merkx (The Scientific World Journal)
The objective of this study was to identify differences in disposition and esterase hydrolysis of ramipril between male and female volunteers. Plasma concentration and area under the concentration-time curve until the last measured concentration (AUCt) data of ramipril and its active metabolite ramiprilat (-diacid) were obtained from a randomised, cross-over bioequivalence study in 36 subjects (18 females and 18 males). Participants received a single 5-mg oral dose of two different formulations of ramipril (Formulation I and II). Plasma ramipril and ramiprilat concentrations were determined according to validated methods involving liquid chromatography-mass spectrometry. A total number of 2 34 available plasma concentration-time curves of both the parent drug and the metabolite could be analysed, and variations (50100% coefficient of variation [CV]) in plasma concentrations of both parent drug and metabolite were found. With both the formulations, the mean plasma concentrations-time curves of males and females were identical. The groups of female and male volunteers showed similar yields (AUCt = mg.h/L) of the metabolite ramiprilat (p = 0.37); however, females showed a higher AUCt/kg than males (p = 0.046). This difference was solely attributed to the difference in body weight between males and females (p = 0.00049). In both male and female groups, a subject-dependent yield of active metabolite ramiprilat was demonstrated, which was independent of the formulation.There is a large variation in the ramiprilat t1/2β (5060% CV). There is a group of subjects who showed a t1/2β of approximately 80 h (15% CV), and two apparent groups with a longer t1/2βfor each formulation (124 h, 22.5% CV; 166 h, 21.6% CV, respectively, p = 0.0013). This variation in the terminal half-life of ramiprilat is not sex related. In all three groups of half-lives, the corresponding Cmax values (mean SD) of ramiprilat in males and females were identical. Thus, with identical Cmax and half-lives, the difference found in the AUCt /kg of ramiprilat must be due to the difference in dose, as the consequence of the difference in body weight, following a standard dose of 5 mg in both males and females.This study showed clearly that despite subject-dependent hydrolysis of ramipril to the active metabolite ramiprilat, the variability in the rate of hydrolysis between males and females is similar. With a fixed dose (5 mg), females received a higher dose/kg than males and consequently showed a higher AUCt/kg of the active metabolite ramiprilat.